A Case Study on Camberwell Sdn. Bhd - Soh, Francis Han Leng (1999)
The purpose of this case study is to determine the marketing competitiveness of Camberwell Sendirian Berhad that will give the company a competitive edge. The marketing competitiveness was analyzed using the SWOT analysis, marketing analysis, financial analysis and SPACE MODEL. SWOT analysis was used to determine the overall strengths, weaknesses, opportunities and threats of the company. Marketing analysis was used to determine competitive aspects with respect to product, price, distribution and promotion strategies of the company. Financial analysis was used to ascertain the company situation in terms of debts and profits. SPACE MODEL is to determine the marketing strategy that is going to deploy by the company.